Increasing the Brand Awareness of PT. Banmadju Mandiriperkasa’s Customers Through A Company Profile Video - Felix Octavius Saverino (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
PT. Banmadju Mandiriperkasa is located at Jl. Pattimura 104b, Kediri. As a tyre retreading company, the main product of PT. Banmadju Mandiriperkasa are both hot and cold retreading systems. Meanwhile, the company also offers a complete tyre sizing for each category of a vehicle from sedan, minibus, bus, truck, forklift, and also OTR (Off the Road). The company’s main problem is the intense competition between the competitors in the global retread tyre market, which causes PT. Banmadju Mandiriperkasa should increase brand awareness to the customers. Therefore, it is better to make a company profile video as a solution to overcome the company’s problem. To gain awareness from the potential customer, the company profile video will be distributed by using social media such as WhatsApp, Instagram, Facebook, and YouTube. By having a company profile video, PT. Banmadju Mandiriperkasa can increase the brand awareness to the potential customers from all over Indonesia. Keywords: retreading company, tyre, awareness, company profile video, potential customers.